Analysis of the Governance Practices for Promoting Sustainable Industrial Parks Development in Ethiopia: Challenges and Prospects - Guteta, Gemechis; Worku, Hailu (International Journal of Sustainable Development & World Policy, 2022)
Because of emerging trends and global socioeconomic dynamism, various opportunities and challenges of industrialization have been experienced in both developed and developing countries. Understanding its vital role in alleviating the sustainability challenges of industrialization, Ethiopia has been undertaking the development of Industrial Parks over the past decade as the significant tool of its industrial policy. However, there is a huge research gap on how to select and implement appropriate governance approach for the process to promote sustainable industrialization in the country. Hence, the primary goal of this study to explore the current bottlenecks of governance practices hampering the Parks’ sustainability, and the key success factors that could be customized and contextually used. It basically applied an exploratory qualitative method primarily based on extensive literature analysis, key informant interviews and observation; thus, revealed the main challenges that impede the sustainability objective of the Parks: political instability and security problems; lack of suitable policies and implementation strategy; inadequate knowledge; weak coordination and limited capacity of stakeholders; and poor information and technology management. It also identified the key success factors from the best practices of global experience. Suggestions have been given on the issues that need emphasis to select and implement effective governance approach for Sustainable Industrial Parks development and operation within the specific context of the country.